Zero fluoroscopy ablation for atrioventricular nodal reentrant tachycardia and typical atrial flutter is equally safe and effective with EnSite NavX, Carto3, and Rhythmia mapping systems - Piros, Katalin; Perge, Péter; Salló, Zoltán; Herczeg, Szilvia; Nagy, Vivien Klaudia; Osztheimer, István; Merkely, Béla; Gellér, László; Szegedi, Nándor (Frontiers in Cardiovascular Medicine, 2023)
Purpose: Our purpose was to compare the procedural characteristics, success rate, and complication rate of the conventional fluoroscopic (CF) and the zero-fluoroscopic (ZF) approach in patients undergoing catheter ablation AVNRT or typical atrial flutter (Aflu).Methods: 186 consecutive patients with an indication for AVNRT or Aflu ablation were enrolled. Based on the operator's preference, the patients were assigned to either CF or ZF group. In the ZF group EnSite NavX, Carto3, or Rhythmia EAMS were used for catheter guidance.Results: The median age was 56 (IQR= 42-68) years, 144 patients had AVNRT, and 42 had Aflu ablation. CF approach was chosen in 123 cases, while ZF in 63 cases. ZF approach was used more often in case of AVNRT patients [56 (39%) vs. 7 (17%), p=0.006] and in the case of female patients [43 (68%) vs. 20 (32%), p=0.008]. Acute procedural success was obtained in all cases. There was no difference in the complication rate (1 vs. 1, p>0.99) between the two groups. No difference was found regarding the procedure time between the CF and ZF groups [CF: 55 (46-60) min, ZF 60 (47-65) min; p=0.487] or in the procedure time for the different EAMS [EnSite NavX: 58 (50-63) min, Carto3: 60 (44.5-66.3) min, Rhythmia: 55 (35-69) min; p=0.887]. A similar success rate was seen at the 3-month follow-up in the two groups [41 (100%) vs. 96 (97%); p=0.55].Discussion: The ZF approach demonstrated non-inferiority in safety and efficacy compared with CF for the AVNRT and Aflu ablations.